Sistem Pemantau Parameter Listrik Menggunakan Protokol Modbus RTU dan BACnet dengan Transmisi Data MQTT - Prasetyo, Yogi Dwi; Utomo, Eko Budi; Gamar, Farida (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2025)
Monitoring electrical power consumption in the PENS Smart Automation Workshop Building is a fundamental step in an effort to optimize efficient resource management. In this research, a monitoring system is developed that is able to accurately measure, record, and store data on the use of electric power in a miniature building model. This system uses the PZEM-004T sensor module as a measuring instrument for electrical parameters combined with Internet of Things (IoT) technology. This system uses the PZEM-004T sensor module as a measuring instrument for electrical parameters combined with Internet of Things (IoT) technology, and an initial study of BACnet communication integration as an additional protocol. The research includes a literature study related to the basic concepts of electric power monitoring, Modbus and BACnet communication protocols, and IoT technology. System design involves the integration of hardware and software with an IoT-based user interface to support data acquisition and visualization. The collected data is sent via MQTT communication to the cloud and displayed in graphical form via the Node-RED platform, allowing real-time monitoring of electric power consumption with an interactive and customizable dashboard display. The test results show that the system is able to record data in real-time and present accurate information, so that it can be the basis for making energy management decisions. This research contributes to the development of a simple energy monitoring system that can improve efficiency in monitoring energy use with a warning if there is an overload.